Control Strategy for Operation Mode Identification of Complex DC Distribution Network - Jie Dong, JianJun Zhao, Huan Liu, Yang Li, Jialin Liu, Meiqi Song, kangmeng Jin (Forest Chemicals Review, 1970)
The unpredictable output of renewable energy sources such as wind power and photovoltaics, the charging and discharging behavior of energy storage systems, the random fluctuation of power load, and the complex change in the topology of the DC distribution network all raise the bar for system-level control and the energy management system of the DC distribution network. This chapter will first create the graph theory model of a DC distribution network, and then offer a control approach for determining the operating mode of a complicated DC distribution network based on the Breadth-First Search (BFS) algorithm in order to address the issues raised above.